Efficacy of directly-observed chloroquine-primaquine treatment for uncomplicated acute Plasmodium vivax malaria in northeast Myanmar: A prospective open-label efficacy trial. Issue 36 (July 2020) - Xu, Shiling; Zeng, Weilin; Ngassa Mbenda, Huguette Gaelle; Liu, Huaie; Chen, Xi; Xiang, Zheng; Li, Cuiying; Zhang, Yanmei; Baird, J. Kevin; Yang, Zhaoqing; Cui, Liwang
Abstract: Background: Chloroquine (CQ) and primaquine (PQ) remain the frontline drugs for radical cure of uncomplicated P. vivax malaria in the Greater Mekong Sub-region (GMS). Recent reports of decreased susceptibility of P. vivax to CQ in many parts of the GMS raise concerns. Methods: From April 2014 to September 2016, 281 patients with uncomplicated P. vivax infection attending clinics in border settlements for internally displaced people in northeast Myanmar were recruited into this study. Patients were treated with standard regimen of 3-day CQ and concurrent 14-day PQ (3.5 mg/kg total dose) as directly observed therapy, and followed for recurrent parasitemia within 28 days post-patency. Results: Within the 28-day follow-up period, seven patients developed recurrent parasitemia, resulting in a cumulative rate of parasite recurrence of 2.6%. Five of the seven parasitemias recurred within two weeks, and two of those failed to clear within seven days, indicating high-grade resistance. Conclusion: Although failure of CQ/PQ treatment of P. vivax was relatively infrequent in northeast Myanmar, this study nonetheless confirms that CQ/PQ-resistant strains do circulate in this area, some of them of a highly resistant phenotype. It is thus recommended that patients who acquire vivax malaria in Myanmar be treated an artemisinin-combination therapy along with hypnozoitocidal primaquine therapy to achieve radical cure.